2018
DOI: 10.1016/j.ajme.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii: Prolonged in-vitro maintenance of virulent tachyzoites in fluid media at low temperatures

Abstract: Background: Prolonged maintenance of infective Toxoplasma gondii tachyzoites (T.g.T.) is an important subject for research purposes. This study aimed to evaluate four serum free fluid media for prolonged in vitro maintenance of T.g.T. Methods: The four fluid media Phosphate buffered saline (PBS) pH 7.2 and Roswell Park Memorial Institute (RPMI-1640) with or without 3% fetal bovine serum (FBS) were evaluated for maintenance of virulent T.g. T. The four media were tested after incubation at three different tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The authors in the recent study concluded that the best condition for T. gondii tachyzoite maintenance was PBS at 4°C, in which the parasite survived for 12 days (Kalani et al 2016a). However, this finding needs further evaluation since other researchers have showed that RPMI-1640 is more successful than PBS in the maintenance of T. gondii tachyzoites (El-Bahy et al 2018). In the present study, we observed that the FBS-supplemented medium is more appropriate than AF for T. gondii tachyzoite maintenance.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The authors in the recent study concluded that the best condition for T. gondii tachyzoite maintenance was PBS at 4°C, in which the parasite survived for 12 days (Kalani et al 2016a). However, this finding needs further evaluation since other researchers have showed that RPMI-1640 is more successful than PBS in the maintenance of T. gondii tachyzoites (El-Bahy et al 2018). In the present study, we observed that the FBS-supplemented medium is more appropriate than AF for T. gondii tachyzoite maintenance.…”
Section: Discussionmentioning
confidence: 92%
“…However, this finding needs further evaluation since other researchers have showed that RPMI-1640 is more successful than PBS in the maintenance of T . gondii tachyzoites (El-Bahy et al 2018 ). In the present study, we observed that the FBS-supplemented medium is more appropriate than AF for T. gondii tachyzoite maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…The results were comparable to other studies in which nutrient-free media, such as NS and PBS, were more suitable than minimum essential media for maintaining T. gondii tachyzoites. Indeed, the media without nutrients, vitamins, carbohydrates, and fats could prolong the viability of free T. gondii tachyzoites better than those containing these kinds of supplements [12,13]. The osmotic coefficient of NS is about 0.93 [21] and is similar to the osmolarity of blood in which circulating tachyzoites have been found in a range of host species [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…It was likely that these biological activities produce harmful materials and cause changes in solution pH, threatening the parasite's survival. In addition, it showed that tachyzoites could survive longer at 4°C than at 18-22°C and 37°C because they retain a minimum metabolic rate [12,13]. Therefore, enrichment of the nutrient solution, such as with the MEM or MEM-FBS media, and at RT might be more harmful to free-living tachyzoites than NS and PBS for the IC condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation